VD_FINDINFO HC / 2012 / 330 vom 23. Mai 2012 - VD Tribunal cantonal (2012)
DROIT DE GARDE | 133 CC, 137 al. 2 CC, 176 al. 1 ch. 1 CC, 176 al. 3 CC, 308 al. 1 let. b CPC (CH), 318 al. 1 let. c ch. 2 CPC (CH)